Spinal deformity in aged zebrafish is accompanied by degenerative changes to their vertebrae that resemble osteoarthritis. - Anthony J Hayes (Public Library of Science (PLoS), 2013)
Age-related degenerative changes within the vertebral column are a significant cause of morbidity with considerable socio-economic impact worldwide. An improved understanding of these changes through the development of experimental models may lead to improvements in existing clinical treatment options. The zebrafish is a well-established model for the study of skeletogenesis with significant potential in gerontological research. With advancing age, zebrafish frequently develop gross deformities of their vertebral column, previously ascribed to reduced trunk muscle tone. In this study, we assess degenerative changes specifically within the bone and cartilage of the vertebral column of zebrafish at 1, 2 and 3-years of age. We show increased frequency and severity of spinal deformities/curvatures with age. Underlying the most severe phenotypes are partial or complete vertebral dislocations and focal thickening of the vertebral bone at the joint margins. MicroCT examination demonstrates small defects, fractures and morphological evidence suggestive of bone erosion and remodeling (i.e. osteophytes) within the vertebrae during aging, but no significant change in bone density. Light and electron microscopic examination reveal striking age-related changes in cell morphology, suggestive of chondroptosis, and tissue remodelling of the vertebral cartilage, particularly within the pericellular micro-environment. Glycosaminoglycan analysis of the vertebral column by HPLC demonstrates a consistent, age-related increase in the yield of total chondroitin sulfate disaccharide, but no change in sulfation pattern, supported by immunohistochemical analysis. Immunohistochemistry strongly identifies all three chondroitin/dermatan sulphate isoforms (C-0-S, C-4-S/DS and C-6-S) within the vertebral cartilage, particularly within the pericellular micro-environment. In contrast, keratan sulfate immunolocalises specifically with the notochordal tissue of the intervertebral disc, and its labelling diminishes with age. In summary, these observations raise the prospect that zebrafish, in addition to modelling skeletal development, may have utility in modelling age-related degenerative changes that affect the skeleton during senescence.